2009
DOI: 10.1155/2009/509258
|View full text |Cite
|
Sign up to set email alerts
|

Acetylsalicylic Acid Use in Patients with Acute Myocardial Infarction and Peptic Ulcer Bleeding

Abstract: The continued use of ASA during AMI and PUD bleeding was variable. However, patients with low-risk ulcers and those who received coronary intervention were more likely to have ASA continued during PUD bleeding. Further studies evaluating the gastrointestinal risk of immediate ASA use in AMI with acute PUD bleeding are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Endoscopic haemostasis is commonly achieved using adrenaline, and cardiac patients may be at theoretical risk of hypertensive crises or arrthymias. 16 Current studies have not reported such occurrences, 3,4,12 and none of our patients experienced any complications. Despite the risks, endoscopy is likely to play an important role in managing this cohort.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Endoscopic haemostasis is commonly achieved using adrenaline, and cardiac patients may be at theoretical risk of hypertensive crises or arrthymias. 16 Current studies have not reported such occurrences, 3,4,12 and none of our patients experienced any complications. Despite the risks, endoscopy is likely to play an important role in managing this cohort.…”
Section: Discussionmentioning
confidence: 52%
“…Diagnostic yield is !79%, 14 ours was 80%, and based on endoscopic findings, increasing evidence suggests that antiplatelet therapy can be safely re-started within seven days of UGIH. 2,4,5 In our study, antiplatelets were safely re-introduced, with PPI cover, after a median of three days. The use of prophylactic PPIs can reduce the risk of UGIH in cardiac patients receiving antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These findings are inconsistent with the results of the present study; this may be due to the small number of patients in the aspirin and clopidogrel groups. Cheung et al (28) demonstrated that patients with AMI who are complicated by peptic ulcer hemorrhage should not continue aspirin where viable; whereas patients who are at low risk of peptic ulcers following PCI treatment should regard aspirin as the preferable choice.…”
Section: Discussionmentioning
confidence: 99%
“…Low dose acetylsalicylic acid administrations to prevent thrombotic stroke or myocardial infarction, also can cause gastrointestinal damage and GI complications. It is reported that, ulcers and erosions have been detected endoscopically in 47.8% of patients who received low dose ASA for more than three months (23)(24)(25)(26). The short-term administration of ASA has been reported to bring out a higher risk compared to long-term administration (27,28).…”
Section: Discussionmentioning
confidence: 99%